KEKUATAN HUKUM SERTIFIKAT HAK MILIK YANG TERBIT DI DALAM KAWASAN HUTAN SEBELUM KELUARNYA KEPUTUSAN MENTERI KEHUTANAN NOMOR SK.453/KPTS-II/1999 - Bambang Puji Mulyo; Achmad Faishal; Suprapto (LPPM STIH Awang Long, 2023)
This land tenure right has been linked to certain land as the object and a certain person or legal entity as the subject or holder of the rights. Mastery or control can be juridical and or can also be physical. Juridical control is based on rights, protected by law and generally gives authority to the right holder to physically control the land being claimed. The relationship between the Indonesian nation and the land is eternal, which means that as long as the Indonesian people are united with the Indonesian nation, the relationship will continue uninterrupted forever. Since the issuance of a certificate of ownership indicating that the area is an area for other uses or outside the forest area and has guaranteed legal certainty. However, the government unilaterally designated their settlements or areas as forest areas since the issuance of Law no. 41/1999 concerning Forestry through the Decree of the Minister of Forestry Number SK.435/KPTS-II/1999. So that the land in the area is designated and determined as a forest area which was previously included in another area of use and in the end the status of the land becomes land attached to a forest area. This means that if land that already has a certificate of ownership is then designated and determined as a forest area, the characteristics of the certificate of ownership will not be fulfilled in the case that the certificate of ownership has the fullest character because the certificate of ownership cannot be the parent for other land rights. and in terms of use it is only limited to physical control but other legal actions cannot be taken against the certificate of ownership. In order to provide legal certainty to holders of land title certificates in this Government Regulation number 24 of 1997, confirmation is given regarding the extent of the strength of certificates, which are stated as a strong means of proof by the Basic Agrarian Law.